Clinical profile and geographical distribution of malaria patients attending a tertiary care centre in Mangaluru, South India - H., Pavithra; Ismail, Imaad Mohammed; Kahar, Ayisha; Bhargav, Sai; Bharadhwaj M. G., Samanth; Kumar, M. Arun; Rajeev, Vishnu (International Journal Of Community Medicine And Public Health, 2019)
Background: Around 0.84 million people contracted malaria in India in the year 2017 and it resulted in 194 deaths. This study was conducted to describe the demographic and clinical profile as well as the geographical distribution of malaria patients attending a tertiary care hospital in Mangaluru. Methods: It was a record based descriptive study. All the malaria cases which were admitted from 1st May 2017 till 30th April 2018 were included in the study. QGIS software was used to plot the cases geographically. Results: A total of 97 malaria cases were present, of which 74.2% were males. The mean age of the participants was 33.4 years. Fever and chills were the most common presenting complaints (94.8% and 85.6% respectively) and thrombocytopenia was the foremost complication. Diagnosis was done using blood smear in 45 cases and rapid diagnostic kit in 59 cases. 8 patients were detected positive by both the tests. Plasmodium vivax (69%) was the most common infection. QGIS plotting of address showed that 61.4% were from Mangaluru block. Rest of the cases were from other parts of Karnataka, Kerala and Bihar. Conclusions: Malaria has a male preponderance and usually affects the economically productive age group. Thrombocytopenia was a common complication, thus necessitating close vigilance on platelet counts in malaria patients. Thick and thin blood smear is recommended to be performed to every case irrespective of their rapid diagnostic kit results. Mangaluru block accounted for 60 cases out of 97 cases which necessitates intensification of preventive measures in the block.